2023
DOI: 10.3390/ijms24076814
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Ciprofloxacin-Based Carbon Dots with High Antibacterial Activity

Abstract: Nowadays, bacterial infections are attracting great attention for the research and development of new antimicrobial agents. As one of the quinolones, ciprofloxacin (CI) has a broad-spectrum, strong antibacterial effect. However, the clinical use of ciprofloxacin is limited by drug resistance. Ciprofloxacin carbon dots (CCDs) with enhanced antibacterial activity and copper-doped ciprofloxacin carbon dots (Cu-CCDs) were synthesized by a simple hydrothermal method. The results of structural analysis and antibacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Thus, in this work, unique modified copper C-CNDs with broad-spectrum antibacterial activity were produced. These C-CNDs may be employed as antibacterial nanomaterials for future uses in the development of antibacterial medications . Folic acid was the starting material utilized by Eman Serag et al to hydrothermally manufacture carbon dots.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, in this work, unique modified copper C-CNDs with broad-spectrum antibacterial activity were produced. These C-CNDs may be employed as antibacterial nanomaterials for future uses in the development of antibacterial medications . Folic acid was the starting material utilized by Eman Serag et al to hydrothermally manufacture carbon dots.…”
Section: Resultsmentioning
confidence: 99%
“…These C-CNDs may be employed as antibacterial nanomaterials for future uses in the development of antibacterial medications. 162 Folic acid was the starting material utilized by Eman Serag et al to hydrothermally manufacture carbon dots. Curcumin was then loaded onto the carbon dots to create a folic acid carbon dot/Curcumin nanocomposite.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported to be many times more effective than norfloxacin and enoxacin. CIP also exhibits good antibacterial action and pharmacokinetic qualities with little adverse effects [ 15 , 16 ]. Traditional Chinese herbs are unique medicinal substances used in traditional Chinese medicine and serve as a significant hallmark distinguishing it from other medical practices.…”
Section: Introductionmentioning
confidence: 99%
“…3 Notably, it was reported that a few properties of the starting raw materials could be retained after carbonization also. 3,5 For example, the carbonized form of a few small drug molecules, such as aspirin 6 levofloxacin, 7 2-methoxy-1, 4-naphthoquinone, 8 and ciprofloxacin, 9 are shown to have better therapeutic properties. Although the mechanisms for the enhanced therapeutic properties are not fully clear, the change in water dispersibility, systemic circulation half-life, cellular uptake, and retention of the carbonized materials are thought to play a crucial role.…”
Section: Introductionmentioning
confidence: 99%